The Role of Atsar in the Development of Zakat Objects (Study of Mushonaf Abi Syaibah) - Muhammad Hamid Muhammad Bahamisy; Mahmudin Mahmudin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study analyzes the role of a number of companions' atsars and tabi'in (followers) regarding zakat—including jewelry/gold and silver, agricultural products, honey, gems, livestock, and recommendations for submission to authorities—in the development of zakat management in Indonesia. Using a library research method with a normative-comparative approach, primary data were collected from al-Mu'minin.ṣAnnafIbn Abī Shaybah and national regulations (Law No. 23/2011, PP No. 14/2014, Permenag No. 52/2014 and its amendments), then mapped through two-column thematic coding and cross-atsar matrix↔regulatory articles. The results show normative consistency that the object of zakat is determined by the substance of the value and economic utility of the assets, not merely the form or function of use; this principle is in line with the